A CRITICAL DISCOURSE ANALYSIS OF GENDER ROLE AND STEREOTYPES IN PRESENT ADVERTISEMENTS – LEADING RESEARCH QUESTIONS BEFORE AND AFTER 2000 (TRAKIA JOURNAL OF SCIENCES, 2025)
This article has the following objectives: 1) to conduct a critical discourse analysis of gender roles and stereotypes in advertising, covering two periods: from 1970 to 2000 and from 2000 to the present; 2) to increase general knowledge about gender roles during both periods, as well as to identify changes in different consumer segments affected by stereotypical advertising. The methodology includes three-dimensional model of Fairclough for critical discourse analysis, which includes description, interpretation and explanation. When conducting the critical analysis for the first period, it was found that more traditional roles of men and women are present in advertising with the impact of a number of schemes for coding attributes for men and women. Scientific research is united around the view of binary gender representation, as the variety of stereotypical images in print and television advertising is also increasing. In the second period, the topic of the affected consumer segments is examined more critically in terms of self-perception, self-esteem, and the sense of self-control when exposed to stereotypical advertising. The latest empirical evidence indicates reactance among consumers of both genders, as the understanding of gender stereotype in advertising is significantly shifting - from a binary concept to a unisex concept. Therefore, scientific progress is established from defining and determining leading stereotypes, to applying non-stereotypical advertising to stereotypical, as well as to facilitating consumer thinking by introducing unique gender roles - for both men and women. The practical applicability of the study is found in facilitating the work of marketers, advertisers and specialists working for better advertising effectiveness.